Theatricality of the Closet : Fashion, Performance, and Subjectivity between Victorian Britain and Meiji Japan - Carriger, Michelle Liu (Book collections on Project MUSE., 2023)
"Michelle Liu Carriger examines fashion and clothing controversies of the nineteenth century, drawing on performance theory to reveal how the apparently superficial or frivolous deeply affects the creation of identity"--